Biocatalytic and Chemo-Enzymatic Approaches for the Synthesis of Heterocycles - Zhao, Fei; Masci, Domiziana; Tomarelli, Elena; Castagnolo, Daniele (Synthesis, 2020)
Heterocycles are ubiquitous structures in nature and can be found in many drugs and chemicals. Biocatalysts, alone or in combination with other metal catalysts, can be exploited for the construction of various heterocyclic rings under mild reaction conditions. This Short Review highlights the recent advances in the development of biocatalytic and chemo-enzymatic methods for the synthesis of both aliphatic and aromatic heterocyclic rings.1 Introduction2 Synthesis of Aliphatic Heterocycles2.1 Piperidines, Pyrrolidines and Piperazines2.2 Other Nitrogen-Containing Aliphatic Heterocycles2.3 Lactones and Lactams2.4 Other Oxygen-Containing Heterocycles3 Synthesis of Aromatic Heterocycles3.1 Pyrroles, Pyridines and Pyrazines3.2 Furans3.3 Bicyclic Aromatic Heterocycles4 Conclusion
Keywords: heterocycles; biocatalysis; chemo-enzymatic cascades; green chemistry; heteroaromatic